A Seventh Century BC Picenian Cloack Clasp Made of Iron, Bone, Bronze and Amber: Reconstruction of a Masterpiece - Mauro Fiorentini (EXARC, 2018)
This article is dedicated to the reconstruction I’ve done in 2017 of a Picenian cloack clasp which is a pretty unique find. It has been found in a prince’s grave dating back to the early 7th Century b.C. and is considered a rare find because only a few similar items have been found in Central Italy, and because of the rare use of amber decorations and bronze plates, that makes this find a true masterpiece. A masterpiece that has been challenging to replicate, but a real pleasure for any Iron Age enthusiast: it is really difficult to remain indifferent in front of this example of craftsmanship and aesthetic taste that captures our gaze even today.